Activation of Delta-Opioid Receptor Protects ARPE19 Cells against Oxygen-Glucose Deprivation/Reoxygenation-Induced Necroptosis and Apoptosis by Inhibiting the Release of TNF-α - Runjie Guo; Ping Chen; Tiantian Fu; Ren Zhang; Yuan Zhu; Nange Jin; Hong Xu; Yong Xia; Xuesong Tian (Journal of Ophthalmology)
Purpose. Retinal ischemia–reperfusion injury (RIRI) is the basis of the pathology that leads to many retinal diseases and induces necroptosis and apoptosis. Tumor necrosis factor-α (TNF-α) is critically involved in necroptosis and apoptosis. Delta-opioid receptor (DOR) activation inhibits TNF-α release in our previous studies, it might prevent necroptosis and apoptosis by inhibiting the release of TNF-α. However, the role of TNF-α and DOR in necroptosis and apoptosis of retinal pigment epithelial (RPE) cells remains largely unknown. Here, we explored the mechanisms of TNF-α and DOR in necroptosis and apoptosis using an oxygen-glucose deprivation/reoxygenation (OGD/R) model of adult retinal pigment epithelial cell line-19 (ARPE19) cells. Materials and Methods. ARPE19 cells were exposed to OGD/R conditions to mimic RIRI in vitro. Cell viability was quantified using the Cell Counting Kit-8 (CCK-8) assay. Morphological changes were observed by inverted microscopy. TNF-α protein levels in cell lysates were measured by enzyme-linked immunosorbent assay (ELISA). The DOR agonist TAN-67 and antagonist naltrindole (NTI) were used to pretreat cells for 1 or 2 hours before OGD24/R36 administration. Calcein acetoxymethylester/propidium iodide (Calcein-AM/PI) and Terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining were used to detect necroptotic and apoptotic ARPE19 cells, respectively. The protein expression of DOR, p-RIP1 (RIP1), p-RIP3 (RIP3), p-MLKL (MLKL), and cleaved Caspase3 (Caspase3) was measured by western blotting. Results. OGD severely damaged ARPE19 cells. Prolonged reoxygenation significantly increased TNF-α level and decreased DOR expression in ARPE19 cells. Pretreatment with the DOR agonist TAN-67 (10 µM) significantly improved ARPE19 cell viability after OGD24/R36 by reducing the number of necroptotic and apoptotic cells. Furthermore, DOR activation significantly inhibited TNF-α release and suppressed the expression of proteins related to necroptosis and apoptosis, including p-RIP1, p-RIP3, p-MLKL, and cleaved Caspase3, after OGD24/R36. This effect was reversed by the DOR antagonist NTI. Conclusion. These results strongly suggest that DOR activation inhibits necroptosis and apoptosis by decreasing TNF-α release, leading to the prevention of OGD/R-induced injury in ARPE19 cells. This study provides an innovative idea for clinical treatment strategies for retinal damage and vision loss due to RIRI.